Determinants of potentially harmful traditional cord care practices among mothers in Ethiopia - Merga, Bedasa Taye; Fekadu, Gelana; Raru, Temam Beshir; Ayana, Galana Mamo; Hassen, Fila Ahmed; Bekana, Miressa; Negash, Belay; Eshetu, Bajrond; Birhanu, Abdi; Mulatu, Gutema; Balis, Bikila (Frontiers in Pediatrics, 2022)
Background: Globally, newborns deaths declined from 5 million in 1990 to 2.4 million in 2019; however, the risk of death in the first 28 days is high. Harmful umbilical cord care contributes to neonatal infection which account for millions of neonatal deaths. This study assessed determinants of potentially harmful traditional cord care practices in Ethiopia using data from nationally representative survey. Methods: Secondary data analyses were employed using data from the 2016 Ethiopian Demographic and Health Survey. Weighted samples of 4402 mothers who gave birth in the last 3 years prior to the survey were included in the analysis. Binary logistic regression was fitted to identify associations of outcome variables with explanatory variables analysis and the results were presented with adjusted odds ratio at 95% confidence interval, declaring statistical significance at a p-value < 0.05 in all analyses. Results: About 13.70% (95%CI: 12.7%, 14.7%) of mothers practice harmful traditional umbilical cord care. Maternal age (25-34 years, AOR=1.77, 95%CI: 1.36, 2.31, 35-49 years, AOR=1.53, 95% CI: 1.07, 2.19), maternal educational (primary; AOR=0.54, 95%CI: 0.41, 0.70 and secondary and above, AOR= 0.61, 95% CI: 0.40, 0.94), parity (Para two, AOR=0.71, 95% CI : 0.55, 0.92), and place of delivery (home delivery, AOR=1.96, 95%CI :1.51, 2.56) were factors associated with potentially harmful traditional umbilical cord care practices. Conclusion: Maternal educational status, parity, maternal age, and place of delivery associated with harmful traditional cord care practices. Thus, improving mother’s education, strengthening antenatal and postnatal care and utilization of institutional delivery would help to reduce harmful traditional cord care practices.